The new merit order: The viability of energy-only electricity markets with only intermittent renewable energy sources and grid-scale storage - Werner Antweiler; Felix Muesgens (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
What happens to the merit order of electricity markets when all electricity is supplied by intermittent renewable energy sources coupled with large-scale electricity storage? With near-zero marginal cost of production, will there still be a role for an energy-only electricity market? We answer these questions both analytically and empirically for electricity markets in Texas and Germany. What emerges in market equilibrium is the 'new merit order'. Our work demonstrates that as long as free entry and competition ensure effective price setting, an efficient new merit order emerges in electricity markets even when the grid is completely powered by intermittent sources with near-zero marginal costs. We find that energy only markets remain viable and functional. – – Was geschieht mit der Merit-Order, wenn die Stromnachfrage allein durch erneuerbare Energiequellen und große Stromspeicher gedeckt wird? Wenn die Grenzkosten der Erzeugung nahezu null sind, kann dann das bisherige Strommarktdesign des Energy-Only-Marktes noch aufrechterhalten werden? Dieser Artikel beantwortet diese Fragen sowohl analytisch als auch empirisch für die Strommärkte in Texas und Deutschland. Es zeigt sich, dass eine effiziente neue 'Merit-Order" entstehen würdet, wenn es freien Marktzugang und Wettbewerb auf den Strommärkten gibt, selbst wenn die Nachfrage vollständig von volatilen erneuerbaren Energie-Quellen mit Grenzkosten nahe Null bedient würde. Zudem zeigt sich, dass reine Energy-Only-Märkte auch weiterhin funktionieren würden.
Keywords: D47; Q41; Q42; L11; 330; Renewable energy; energy storage; electricity markets